Accuracy of Consumer‐marketed smartphone‐paired alcohol breath testing devices: A laboratory validation study. (9th May 2021) - Delgado, Mucio Kit; Shofer, Frances; Wetherill, Reagan; Curtis, Brenda; Hemmons, Jessica; Spencer, Evan; Branas, Charles; Wiebe, Douglas J.; Kranzler, Henry R.
Abstract: Background: Although alcohol breath testing devices that pair with smartphones are promoted for the prevention of alcohol‐impaired driving, their accuracy has not been established. Methods: In a within‐subjects laboratory study, we administered weight‐based doses of ethanol to two groups of 10 healthy, moderate drinkers aiming to achieve a target peak blood alcohol concentration (BAC) of 0.10%. We obtained a peak phlebotomy BAC and measured breath alcohol concentration (BrAC) with a police‐grade device (Intoxilyzer 240) and two randomly ordered series of 3 consumer smartphone‐paired devices (6 total devices) with measurements every 20 min until the BrAC reached <0.02% on the police device. Ten participants tested the first 3 devices, and the other 10 participants tested the other 3 devices. We measured mean paired differences in BrAC with 95% confidence intervals between the police‐grade device and consumer devices. Results: The enrolled sample ( N  = 20) included 11 females; 15 white, 3 Asian, and 2 Black participants; with a mean age of 27 and mean BMI of 24.6. Peak BACs ranged from 0.06–0.14%. All 7 devices underestimated BAC by >0.01%, though the BACtrack Mobile Pro and police‐grade device were consistently more accurate than the Drinkmate and Evoc. Compared with the police‐grade device measurements, the BACtrack Mobile Pro readings were consistently higher, the BACtrack Vio and Alcohoot measurements similar, and the Floome, Drinkmake, and Evoc consistently lower. The BACtrack Mobile Pro and Alcohoot were most sensitive in detecting BAC driving limit thresholds, while the Drinkmate and Evoc devices failed to detect BAC limit thresholds more than 50% of the time relative to the police‐grade device. Conclusions: The accuracy of smartphone‐paired devices varied widely in this laboratory study of healthy participants. Although some devices are suitable for clinical and research purposes, others underestimated BAC, creating the potential to mislead intoxicated users into thinking that they are fit to drive. Abstract : This laboratory study of healthy participants found the accuracy of consumer smartphone‐paired alcohol breath testing devices varied widely relative to venous blood alcohol content (BAC) and BAC estimated by a police grade breath testing device. Although some smartphone‐paired alcohol breath testing devices are suitable for clinical and research purposes, others significantly underestimated BAC creating the potential to mislead intoxicated users to think that they are fit to drive.